Two potential self-activated orthoborates Cd4NdO(BO3)3 and Ca3Nd3(BO3)5: growth, crystal structures and optical properties. (4th January 2016) - Wang, Xing; Xia, Mingjun; Li, R. K.
Abstract : Different arrangements of NdO n polyhedra in the two crystal structures can result in a huge difference of their fluorescence lifetime. Abstract : Two neodymium orthoborate crystals of Cd4 NdO(BO3 )3 and Ca3 Nd3 (BO3 )5 were successfully grown using the flux method. Single crystal X-ray diffraction exhibits that Cd4 NdO(BO3 )3 crystallizes in the monoclinic space group of Cm with unit cell parameters a = 8.0536(14) Å, b = 15.872(2) Å, c = 3.5364(6) Å, β = 100.268(7)° and Ca3 Nd3 (BO3 )5 has a hexagonal space group of P 63 mc with cell parameters a = 10.4864(2) Å, c = 6.2665(1) Å. Both compounds have high Nd 3+ concentration with 4.5 × 10 21 ions per cm 3 in Cd4 NdO(BO3 )3 and 1.0 × 10 22 ions per cm 3 in Ca3 Nd3 (BO3 )5, respectively. The absorption and emission spectra as well as decay curves for the 4 F3/2 to 4 I11/2 transition of Nd 3+ ions in the two compounds were measured at room temperature. The spectra indicate that both two crystals are potential materials as self-activated microchip laser media due to high Nd 3+ contents.